Mechanistic Pathways of Selenium in the Treatment of Graves’ Disease and Graves’ Orbitopathy - Marinò, Michele; Dottore, Giovanna Rotondo; Leo, Marenza; Marcocci, Claudio (Hormone and Metabolic Research, 2018)
Based on the role of oxidative stress in the pathogenesis of Graves’ hyperthyroidism and Graves’ orbitopathy, the use of the antioxidant agent selenium has been proposed and several studies on the subject have been conducted, both in vitro and in vivo. Whereas a true benefit related to the use of selenium in patients with Graves’ hyperthyroidism has been questioned, its use in patients with mild Graves’ orbitopathy is generally believed to be beneficial because of which selenium has entered in the clinical practice for this eye condition.
Keywords: thyrotoxicosis; Graves’ disease; hyperthyroidism